Peningkatan Hardskill Pembuatan Mesin Pelet Ikan Mandiri Bagi Kelompok Masyarakat Pembudidaya Ikan Nila Peningkatan Hardskill Pembuatan Mesin Pelet Ikan Mandiri Bagi Kelompok Masyarakat Pembudidaya Ikan Nila - andreas pujianto; M. Zaki Latif A.; Sigit Deddy Purnomo Sidhi; Akhmad Nurfauzi; Djoko Prasetyo (Buletin SWIMP, 2021)
The price of feed is one of the biggest contributors to production costs in fish farming. The purpose of this community service activity is to provide knowledge and skills on manufacturing independently fish pellet machines for the the tilapia farmer community in Klawasi village. The training is carried out by providing theoretical material about independent feed and pellet machine design as well as the practice of assembling pellet machine components and operating to test the performance of the pellet machine. The training was held at the Politeknik Kelutan dan Perikanan Sorong and was attended by 10 participants from the tilapia farmer community. The result of the training output is the production of two fish pellet machines that are ready to operate. The results of the satisfaction survey showed that 80% of participants strongly agreed about the good implementation of the training activities.